FIRST RECORD OF SIX SPECIES OF Agriotes spp (Coleoptera: Elateridae) IN THE Middle OF IRAQ.* - Redha S. Al-Jorany (Mesopotamia Journal of Agriculture)
This study were carried in 3 different fields in the middle of Iraq to detect and determine the seasonal occurrence of Agriotes spp. Nine sex pheromones of Agriotes spp. and three pheromone traps (YATLOR F) were used for each of these species which baited with the specific pheromone from 1/9/2008 – 1/9/2009 in the College of Agriculture – Abu – Ghraib/ provenance of Baghdad and Al- Nile / provenance of Babylon, while in Al- Radhwania/ Baghdad were used through May – June. Pheromone dispensers were replaced every 6 weeks, Six Agriotes species: A. proximus (Schwarz)، A. lineatus (Linnaeus)، A. brevis (Candeze)، A. obscurus (Linnaeus)، A. sputatur (Linnaeus) ، A. ustulatus (Schaller) and A. litigious (Rossi) were caught by sex pheromone traps. This is the first record of these species in the middle of Iraq. The seasonal occurrence of these species lasted from the second half of March to the first half of August and the most abundant species were A. proximus and A. sputator.